BLAKE’S RELIGIOUS VIEW IN THE POEM “THE LITTLE BLACK BOY” - Prapanca, Agni Sukma (LANTERN (Journal on English Language, Culture and Literature), 2015)
Poetry is one of the kinds of literary works that can be used by the author to say his or her feeling based on the situation and condition at the time the work is written. William Blake is a big poet. He writes most of his work to criticize the situation of the society. This paper has a purpose to analyse the poem of William Blake entitled “The Little Black Boy”. The writer wants to analyse and examine the intrinsic and extrinsic elements of the poem. The poem entitled “The Little BlackBoy”has three kinds of figures of speech, there are denotation and connotation, imagery, and simile. The writer uses sociological theory to analyse the extrinsic discussions. The discussions are about the relation between the society and the poem, and the religious view of William Blake through the poem. The writer finds that in this poem, William Blake uses a lot of words that can be interpreted as his thought about situation at that time.